Identification of chemical compounds of Nardostachys Jatamansi essence available in Iran - Ghassemi-Dehkordi Nasrolah; Sajjadi Ebrahim; Shafiei-Koojani Hamed; Keshvari Mahtab; Hoseini Seyyed-Masih (Shahrekord University of Medical Sciences, 2014)
Introduction: With regard to using drugs with plant origin and with the aim of suitable use of these types of drugs and preventing them to be abused, it is necessary to determine the standards of these plants. The aim of the present study was to identify and study chemical compounds of Nardostachys Jatamansi essence in Iran and define monograph of this plant for the Iranian plant pharmacopeia. Methods: In an experimental study the Nardostachys Jatamansi specimen was prepared from the market in Iran. The essence of the plant was prepared by the hydro-distillation in Clevenger apparatus. Essence was obtained as a greenish yellow oil layer with the 0.07 % yield. The essence compounds were identified quantitatively by Gas Chromatography-Mass Spectroscopy (GC/MS) method. Results: Totally, 29 compounds were identified in Nardostachys Jatamansi essence. The retention indexes (RI) were only similar with overall standard values in two compounds like mesitylene and P-cymene. In this line the RI values about three compounds of valerenic acid, palmitic acid, and valerenyl isovalerate were determined significantly higher than standard values of RI. Conclusion: The essence prepared from the Nardostachys Jatamansi plant in Iran was different in terms of some compounds and components including valerenic acid, palmitic acid, and valerenyl isovalerate and so it is necessary to identify and register quality and quantity characteristics of compounds available in this plat in the Iranian medicinal plants pharmacopeia.